2007
DOI: 10.1111/j.1365-2672.2006.03271.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of compost maturity and Actinobacteria populations during full-scale composting of organic household waste

Abstract: Aims:  This study investigates changes in microbiological and physicochemical parameters during large‐scale, thermophilic composting of a single batch of municipal organic waste. The inter‐relationships between the microbial biomass and community structure as well as several physicochemical parameters and estimates of maturation were evaluated. Methods and Results:  Analyses of signature fatty acids with the phospholipid fatty acid and ester‐linked methods showed that the total microbial biomass was highest du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 47 publications
1
31
0
3
Order By: Relevance
“…Pérez et al (2002) and Nakasaki et al (2009) showed that actinobacteria produce an active enzyme to degrade lignocellulotic compounds. Tuomela et al (2000); Steger et al (2007) and Xiao et al (2011) have shown that actinomycetes are activated later and contribute to the degradation of recalcitrant compounds and the formation of the stable compounds of ''humic substance''.…”
Section: Enumeration Of Mesophilic and Thermophilic Indigenous Microfmentioning
confidence: 99%
See 2 more Smart Citations
“…Pérez et al (2002) and Nakasaki et al (2009) showed that actinobacteria produce an active enzyme to degrade lignocellulotic compounds. Tuomela et al (2000); Steger et al (2007) and Xiao et al (2011) have shown that actinomycetes are activated later and contribute to the degradation of recalcitrant compounds and the formation of the stable compounds of ''humic substance''.…”
Section: Enumeration Of Mesophilic and Thermophilic Indigenous Microfmentioning
confidence: 99%
“…Chroni et al (2009) explained that the thermophilic fungi exhibited a small increase as temperature rose in the first month of composting, stabilizing thereafter. Steger et al (2007), showed that fungi and actinobacteria commonly proliferate during periods with comparatively low temperatures (\45°C). Several authors show that the final phase, which includes both coolingdown and maturation stages, is characterised by the development of a new mesophilic fungal community (Finstein and Morris 1975;Ishii et al 2000).…”
Section: Enumeration Of Mesophilic and Thermophilic Indigenous Microfmentioning
confidence: 99%
See 1 more Smart Citation
“…Sự tồn tại các nhóm vi sinh vật theo từng giai đoạn và phụ thuộc vào nguồn carbon hữu cơ hòa tan, tỷ lệ thay đổi C/N [2], cũng như nhiệt độ và pH trong các giai đoạn phân hủy trong báo cáo của Cahyani (2003) [1] cho thấy cộng đồng vi khuẩn trong phân bón của rơm rạ như Alphaproteobacteria trong nguyên liệu, Bacillus và Actinomycetes ở giai đoạn ưa nhiệt và Cytophaga và Clostridial. Theo kết quả nghiên cứu của Steger (2007) [13] cho thấy thay đổi thành phần trong cộng đồng Actinobacteria trong quá trình ủ thải hữu cơ theo quy mô của hộ gia đình. Trong thí nghiệm này, chúng tôi chọn phân chuồng ủ từ các hộ gia đình theo phuơng thức truyền thống, nên quá trình tách chiết và tinh sạch cũng như nhân bản đoạn gene 16S rDNA cho kết quả thường không ổn định xem hình 1.…”
Section: Kết Quả Và Thảo Luậnunclassified
“…The internal tissues are nutrient rich and have a pH nearly neutral because the principal storage polymer is starch. During the composting process, various parameters including C:N ratio, composting temperature, pH of the finished product, moisture content and the presence of potential pathogens such as coli form bacteria are used to assess the quality and stability of the compost (Wu and Ma 2002;Steger et al, 2007;Sanmanee et al, 2011). In the present study, a simple microbiological process, this could provide a solution to the problem of kitchen waste disposal, and for recycling of solid waste into useful manure by the action of decomposing bacteria.…”
Section: Introductionmentioning
confidence: 99%